2012
DOI: 10.5504/bbeq.2012.0023
|View full text |Cite
|
Sign up to set email alerts
|

One Fish, Two Fish, Old Fish, New Fish—Is the Biodiversity of Bulgarian Native Brown Trout (S. Trutta Fario) Populations at Risk?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These enhancements have included releases of artificially reared stocks or escapes of large numbers of individuals characterized by lower fitness (Satake and Araki 2011;Baskett et al 2013;Milot et al 2013;Naish et al 2013) and lower genetic diversity have been reported for some species, including Adriatic sturgeon (Boscari and Congiu 2014), Korean starry flounder ) and black sea bream in Japan (Blanco Gonzalez and Umino 2009). Other effects have been introductions of nonindigenous populations, such as salmon in Poland (Poćwierz-Kotus et al 2015a;Bernaś et al 2016); or alien populations of the same species and their subsequent hybridization a Corresponding author: rwenne@iopan.gda.pl with local native populations, as with salmon and brown trout in Bulgaria (Chelenkova et al 2012), Norway (Thaulow et al 2012), Hungary (Horváth et al 2013) and in Spain (Madeira et al 2005), pikeperch in Finland (Salminen et al 2012); unintentional escapes from hatcheries as red sea bream in Japan (Blanco Gonzalez et al 2015), salmon in Norway (Liu et al 2013) and Canada (Fraser et al 2008). Accidental or deliberate introductions of exotic and invasive species to new environments, often beneficial economically, causes distortions in the functioning of local ecosystems and can threaten native populations of fish and shellfish, as in the case of brown trout in Japan (Hasegawa and Maekawa 2008), Patagonia (Vigilano et al 2007;Young et al 2010) and in North America (Turek et al 2016), mussel Mytilus in Europe and South Africa (Kijewski et al 2009;McQuaid et al 2015 and oyster Crassostrea gigas (Carlton 1979;Meehan et al 1989;Miller et al 2012;Lallias et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These enhancements have included releases of artificially reared stocks or escapes of large numbers of individuals characterized by lower fitness (Satake and Araki 2011;Baskett et al 2013;Milot et al 2013;Naish et al 2013) and lower genetic diversity have been reported for some species, including Adriatic sturgeon (Boscari and Congiu 2014), Korean starry flounder ) and black sea bream in Japan (Blanco Gonzalez and Umino 2009). Other effects have been introductions of nonindigenous populations, such as salmon in Poland (Poćwierz-Kotus et al 2015a;Bernaś et al 2016); or alien populations of the same species and their subsequent hybridization a Corresponding author: rwenne@iopan.gda.pl with local native populations, as with salmon and brown trout in Bulgaria (Chelenkova et al 2012), Norway (Thaulow et al 2012), Hungary (Horváth et al 2013) and in Spain (Madeira et al 2005), pikeperch in Finland (Salminen et al 2012); unintentional escapes from hatcheries as red sea bream in Japan (Blanco Gonzalez et al 2015), salmon in Norway (Liu et al 2013) and Canada (Fraser et al 2008). Accidental or deliberate introductions of exotic and invasive species to new environments, often beneficial economically, causes distortions in the functioning of local ecosystems and can threaten native populations of fish and shellfish, as in the case of brown trout in Japan (Hasegawa and Maekawa 2008), Patagonia (Vigilano et al 2007;Young et al 2010) and in North America (Turek et al 2016), mussel Mytilus in Europe and South Africa (Kijewski et al 2009;McQuaid et al 2015 and oyster Crassostrea gigas (Carlton 1979;Meehan et al 1989;Miller et al 2012;Lallias et al 2015).…”
Section: Introductionmentioning
confidence: 99%